Understanding the role of the first language (L1) in instructed second language acquisition (ISLA): Effects of using a principled approach to L1 in the beginner foreign language classroom. (September 2022) - de la Fuente, María J.; Goldenberg, Carola
This study investigated whether second language (L2) classroom instruction that incorporates a principled approach into the use of the first language (L1) by students and instructors has an effect on beginning learners' development of L2 speaking and writing proficiency, compared to L2-only instruction, over the course of one semester. Participants were 54 students of Spanish enrolled in six sections of a university-level Elementary Spanish course. The six intact classes, exposed to the same task-based curriculum, were randomly assigned to two experimental groups (–L1 and +L1). For the –L1 group, instruction and interaction were conducted exclusively in the L2, whereas instruction and interaction in the +L1 group included specific uses of the L1. A pretest–posttest design was used to measure change in speaking and writing proficiency. Effects were assessed using the STAMP 4 test, a standardized measure of proficiency. Results indicated that courses under both conditions promoted improvements in speaking and writing. However, students in the +L1 condition improved significantly more than those in the control –L1 group, both in speaking and writing. This points to a potentially more important role for the L1 in the development of an L2. Pedagogical implications are discussed, and directions for further research are offered.